The Battle of the Sexes for Stroke Therapy: Female- Versus Male-Derived Stem Cells - Kaneko, Yuji; Pabon, Mibel M.; Dailey, Travis; Weinbren, Nathan L.; Rizzi, Jessica; Tamboli, Cyrus; Vasconcellos, Julianne; Kuzmin-Nichols, Nicole; Sanberg, Paul R.; Eve, David J.; Tajiri, Naoki; Borlongan, Cesar V. (CNS & Neurological Disorders - Drug Targets, 2013)
Cell therapy is a major discipline of regenerative medicine that has been continually growing over the last two decades. The aging of the population necessitates discovery of therapeutic innovations to combat debilitating disorders, such as stroke. Menstrual blood and Sertoli cells are two gender-specific sources of viable transplantable cells for stroke therapy. The use of autologous cells for the subacute phase of stroke offers practical clinical application. Menstrual blood cells are readily available, display proliferative capacity, pluripotency and angiogenic features, and, following transplantation in stroke models, have the ability to migrate to the infarct site, regulate the inflammatory response, secrete neurotrophic factors, and have the possibility to differentiate into neural lineage. Similarly, the testis-derived Sertoli cells secrete many growth and trophic factors, are highly immunosuppressive, and exert neuroprotective effects in animal models of neurological disorders. We highlight the practicality of experimental and clinical application of menstrual blood cells and Sertoli cells to treat stroke, from cell isolation and cryopreservation to administration.
Keywords: autologous